The Impact of Competence and Work Discipline on Employee Performance at XLSmart - Broto Wiyono; Sri Wahyuningsih; Yeti Rohayati; Dwiwahjuni Wulandari (Annals of Management and Organization Research, 2026)
Purpose: This study aims to examine the effect of competence and work discipline on employee performance at XLSmart Jakarta. The focus is to understand how these two human resource dimensions contribute to organizational success in a highly competitive business environment Research Methodology: The research adopts a quantitative approach with descriptive and verificative methods. The population consists of 400 employees, and a sample of 80 respondents was determined using the Slovin formula. Data were collected through questionnaires and analyzed using SPSS version 25. Validity and reliability tests confirmed that all indicators were appropriate and consistent for measuring the study variables. Results: The findings show that both competence and work discipline have a significant positive effect on employee performance. The regression model Y = 26.423 + 0.226X1 + 0.178X2 explains that improvements in competence and discipline lead to better performance outcomes. The coefficient of determination (R²) of 0.627 indicates that 62.7% of performance variance is explained by competence and discipline, while 37.3% is due to other factors not investigated in this study. Conclusions: Competence and discipline are essential drivers of employee performance. Organizations need to strengthen training programs and enforce discipline consistently to maximize productivity. Limitations: This study is limited to one company and uses cross-sectional data, which may restrict generalizability. Contribution: Explain how this study can contribute. To whom, what study area, discipline, etc.